Permodelan Sistem Informasi Penjualan Barang Menggunakan Metode Scrum - Mustika, Ana (Journal of Data Science and Information Systems, 2024)
A sales information system is an infrastructure specifically designed to manage and support the sales process of a company. This research aims to design a sales information system by applying the Scrum method so as to accelerate the sales information system design process. The Scrum method in modeling goods sales information systems also promotes close collaboration between development teams, stakeholders, and end users. Through regular meetings such as Sprint Planning, Daily Standup, and Sprint Review, teams can openly communicate about project progress, obstacles faced, and changing needs that may arise. The results of black-box testing show results of 100% in accordance with the goods sales information system, providing an overview of the readiness of the system to meet the functional and performance requirements that have been set.